2013
DOI: 10.1155/2013/130989
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Aqueous Extract of Stem Bark of Cissus populnea on Ferrous Sulphate- and Sodium Nitroprusside-Induced Oxidative Stress in Rat’s Testes In Vitro

Abstract: Cissus populnea are plants associated with a myriad of medicinal uses in different parts of the world and are good sources of carotenoids, triterpenoids, and ascorbic acid. The antioxidant properties and inhibitory effect of water extractible phytochemicals from stem bark of C. populnea on FeSO4 and sodium nitroprusside- (SNP-) induced lipid peroxidation in rat testes were investigated in vitro. The results revealed that the extract was able to scavenge DPPH radical, chelate Fe2+ and also had a high reducing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Plant-based bioactive phytochemicals such as polyphenols and alkaloids have shown promising neuroprotective potentials in both in vitro [15] and in vivo rat [16, 17] and drosophila models [18, 19]. Green leafy vegetables form a major constituent of local diets and are the major sources of plant bioactive phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-based bioactive phytochemicals such as polyphenols and alkaloids have shown promising neuroprotective potentials in both in vitro [15] and in vivo rat [16, 17] and drosophila models [18, 19]. Green leafy vegetables form a major constituent of local diets and are the major sources of plant bioactive phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…2 [17][18][19][20] The metabolism of the drug has been widely studied both in experimental animals and humans as classical inductor of oxidative stress. 21,22 From the study, the group administered with SNP only showed significant increase in MDA concentration while rhodanese and GSH activity showed significant decrease compared to the control which may be attributed to the decomposition of SNP. The decrease observed in rhodanese activity and GSH may be attributed to participation in cyanide detoxification and antioxidant activity.…”
Section: Discussionmentioning
confidence: 90%
“…Oxidative injury was induced in vitro using earlier established protocols with slight modifications (Akomolafe et al, 2013;Kizil et al, 2010). Briefly, 100 µl of the hepatic tissue supernatant was incubated with 15-240 μg/ml each of hexane, DCM, and ethanol extracts in the presence of 0.1 mM of FeSO 4 at 37 °C for 30 min.…”
Section: Induction Of Oxidative Injurymentioning
confidence: 99%